Rhodian-Style Fractions Bearing Apollo and a Rose: Mint at Phanagoria: _________________________________ - Abramzon, Mikhail; Kuznetsov, Vladimir (Acta Archaeologica Lodziensia, 2019)
Among the coins found on the Taman Peninsula, in the neighourhood of Ancient Phanagoria, the silver coins depicting a rose (described as a diobol) have been recently found. These coins are without any inscription but their iconography is similar to that on Rhodian coins. As coins of similar iconography but bearing the inscription ΦΑΝΑ[ΓΟ] / ΡΙΤΩΝ have been found at Phanagoria, the new coins have been attributed to the Phanagorian mint. The new finds of such coins at Phanagoria confirms that Rhodian-style coins were struck at her mint.